(untitled) (Journal of Comparative Social Work, 2025)
Productive ageing as a global agenda and initiative aims to improve the productivity of the older population, evidenced to be gradually increasing and living longer. Older people are a significant resource in most African communities. Understanding their productive ageing practices and experiences in their localities informs social work practitioners on how they can promote and support productivity for other older people in their respective communities. This study conducted in Iringa, Tanzania explored two questions: (i) What practices do retired primary school teachers engage in to achieve productive ageing in their local communities? (ii) In what ways can social work practitioners integrate the practices of productive ageing towards enhancing the well-being of older people in their communities? We applied a case study design that involved 14 purposively selected participants, with data gathered through interviews and thematically analysed. The findings reveal that older people actively engage in several practices and activities that nurture their productive ageing, while empowering them to be relevant and providing support within their local communities. Self-care practices revealed include proper hygiene, diet and exercise engagement. Furthermore, the types of socio-economic activities and participation that include farming, livestock keeping, self-help groups and community shared events are shaped and influenced by cultural factors, community values, individual preferences, the abilities of older people and the availability of resources at their disposal. The productive ageing practices and engagements are practical and relevant to rural contexts. Despite commonalities in some aspects of productive ageing informed by international literature, this study reveals distinct variations in activities and other dimensions of productive ageing, such as self-care. Consequently, this study highlights the necessity for upholding and encouraging local and context-based productive ageing practices that have proven to be beneficial, practical, relevant and responsive to local realities.